Pragmatic Analysis on Staff Related Issues in Selected Hospitals - Roja, K.; Kusuma, G.D.V.; Kumar, B. Ravi (International Journal of Business and Management Future, 2018)
For the efficient management of an organization, it is pertinent that personnel working in different capacities in the different departments make possible friendly relations. Superiors would remain superiors even if they are influenced by ego. The supervisors acting like a superior and behaving like an officer/administrator, the possibilities of degeneration in the relations can’t be overruled. The service of hospitals based on the staff it is essential for all the personnel irrespective of the rank and position they hold make sincere and honest efforts to accomplish the organizational goals. The present study is an attempt to portray the staff related issues in selected hospitals like GEMS, KIMS, RIMS, GMR.